FROM GUIDES TO INTERPRETERS LESSONS FROM HERITAGE INTERPRETATION TRAINING IN TERNATE, NORTH MALUKU, INDONESIA - RW (Bill) Carter; Roswita Aboe; Rahula Perera; Kris Syamsudin (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2021)
With a perceived need to improve the interpretation quality of guiding in the 17th century Dutch-colonial Fort Oranje, six on-line workshops were conducted for professional guides and historical society members from Ternate, North Maluku. The workshops included sessions on historical context, fort features, guiding and interpretation good practice principles, tour planning and delivery. Self-assessment evaluations by participants revealed lack of confidence with their level of historical knowledge and in applying interpretive approaches that would enhance a tour of the fort more enjoyable and meaningful for tourists. Limitations of the on-line medium for training were identified by presenters relating to the need for practical on-site tutoring and integration of historical context and content with places, interpretive principles, and visitor expectations. Exposure of participants to novel ideas and approaches to guiding was constrained by language, participant experience of quality interpretation, and face-to-face mentoring. While the content of the training program can be adapted for improving interpretive guiding in geoparks, there is probably value in some restructuring to include a two-stage process that starts with training-of-trainers.